PENGARUH PROBLEM BASED LEARNING DAN DIRECT INSTRUCTION TERHADAP KEMAMPUAN MENULIS TEKS NARASI SISWA KELAS XII SMA NUSANTARA LUBUK PAKAM - Yovita Simangunsong; Sadieli Telaumbanua; Yenita Br Sembiring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of the Problem Based Learning and Direct Instruction models on the writing ability of narrative texts of grade XII students of SMA Nusantara Lubuk Pakam. The method used was quantitative with a quasi-experimental design, using problem based learning and direct instruction class samples. The results showed that the Problem Based Learning model had a positive and significant effect on students' writing ability, while Direct Instruction did not show a significant effect. In addition, there was a significant difference between the two models, where Problem Based Learning proved to be more effective. The conclusion in this study is that the Problem Based Learning learning model has a significant effect on improving students' writing ability compared to Direct Instruction, which proved to be less effective. This shows that a problem-based learning approach is more able to encourage students to develop writing skills optimally.